STUDENTS' PERCEPTION TOWARD THE TRANSITION OF ONLINE TO OFFLINE LEARNING ENGLISH AFTER COVID-19 PANDEMIC AT A SENIOR HIGH SCHOOL IN BATANGHARI REGENCY JAMBI PROVINCE - Desmasari, Anisa (Langue (Journal of Language and Education), 2023)
This research aims to find out students' perceptions and the obstacles experienced by students towards the transition of English learning from online to offline after the Covid-19 pandemic in a high school in Batanghari district, Jambi province. This research is qualitative research with a case study approach. The informants in this research were eleventh grade students and English teachers who taught eleventh-grade. The research location is a school in Batanghari district, Jambi province. Data collection techniques through interview. The results of the data analysis showed that all students responded well to the transition from online to offline learning. This perception is shown to emphasize that online learning is not always effective due to the lack of supporting equipment at school. In addition, the students were not fully engaged during online learning and they could not participate as effectively as offline learning. This research shows, all students have felt bored to do online learning at home. Because what students get during online learning is only receiving materials, after that, students do the tasks given by the teacher. When offline students get a real learning atmosphere in class, and can interact directly with friends and teachers. In addition, students still need time to adapt when switching from online to offline learning. Students show the same attitude when studying online even though they have studied offline at school. In this case, the role of the teacher is needed by students at school because it helps to generate learning motivation, direct students in class during the learning process, and improve new students’ activities.